Nuevos datos sobre el género Tulostoma (Gasteromycetes) en España. IV - Calonge, Francisco de Diego; Llimona i Pagès, Xavier; Martín Esteban, María Paz (Revista Catalana de Micologia, 2011)
Eleven taxa of Tulostomaare mentioned in this article, from which T crassipes represents a new record for Spain and T aff.bruchi is mentioned for the second time. Other common species such as T brumale, T caespitosum,T cyclophorum, T fimbriatum, T giovanellae, T kotlabae, T lloydii, T subsquamosum andT squamosum are recorded in new localities, too.